Steel Slag as New Catalyst for the Synthesis of Fames from Soybean Oil - Michele Casiello (Catalysts, 2021)
For the first time, secondary steel slag, the material directly coming from ladle treatments, is used as a catalyst for the biodiesel production without undergoing any preliminary chemical or thermal modifications. Catalytic material 1, which has been pre-ground to sizes below 230 mesh, has been characterized for the surface textural properties and used as a catalyst in the transesterification of triglycerides of soybean oil to produce biodiesel. Reaction conditions were optimized by DOE method, revealing no interdependence between reaction parameters and results, and showed a catalytic activity comparable with that of an analogous slag-deriving catalyst reported in the literature.